Recent advances in laboratory assessment of emotion regulation. (June 2015) - Seeley, Saren H; Garcia, Emmanuel; Mennin, Douglas S
Highlights: Lab assessment may help to promote emotion regulation as a viable scientific construct. Recent advances share the aim of increasing utility, validity, and reliability. Combining different methods aids our understanding of mechanisms and phenomenology. Abstract : Over the past 15 years, the emotion regulation perspective has been widely integrated into theoretical and applied contexts in clinical psychology and beyond. Recent refinements to behavioral, subjective, psychophysiological and neuroimaging methods allow emotion regulation to be captured and assessed in the laboratory with greater precision. Technological advances enabling investigators to leverage information from multiple modalities are increasingly accessible, and as such, will further efforts to generate testable hypotheses about specific mechanisms implicated in emotion regulation and difficulties therein. In combination with theory-driven design, progressively sophisticated methods for laboratory assessment have potential to further emotion regulation as both a valid scientific construct and a useful paradigm for human emotion and behavior that has applicability to both clinical and non-clinical contexts.